2016
DOI: 10.1007/s13277-016-5044-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction: could it be considered as speed bump on tumor progression road?

Abstract: Dietary restrictions, including fasting (or long-term starvation), calorie restriction (CR), and short-term starvation (STS), are considered a strong rationale that may protect against various diseases, including age-related diseases and cancer. Among dietary approaches, STS, in which food is not consumed during designed fasting periods but is typically not restricted during designated feeding periods, seems to be more suitable, because other dietary regimens involving prolonged fasting periods could worsen th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 88 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…Previous studies also showed that tumor suppressor genes, daf-16/ Foxo, daf-18/Pten, and lin-35/Rb are required for promoting C. elegans starvation survival (Baugh and Sternberg 2006;Cui et al 2013). Starvation or fasting has recently been investigated in cancer therapy (Naveed et al 2014;Cangemi et al 2016), as tumor cells are thought to be more susceptible to starvation due to the Warburg effect (Iansante et al 2015). Results from this study and previous work using C. elegans may suggest that cancer cells, that commonly harbor mutations in tumor suppressor genes, are highly sensitive to starvation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that tumor suppressor genes, daf-16/ Foxo, daf-18/Pten, and lin-35/Rb are required for promoting C. elegans starvation survival (Baugh and Sternberg 2006;Cui et al 2013). Starvation or fasting has recently been investigated in cancer therapy (Naveed et al 2014;Cangemi et al 2016), as tumor cells are thought to be more susceptible to starvation due to the Warburg effect (Iansante et al 2015). Results from this study and previous work using C. elegans may suggest that cancer cells, that commonly harbor mutations in tumor suppressor genes, are highly sensitive to starvation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, cancer cells are selectively killed, mainly by autophagy. On the contrary, normal starved cells halt cell cycle through insulin-like growth factor-1 and shift energy deficiency towards survival (Buono and Longo 2018; Cangemi et al 2016; Lee et al 2010). Although reports concerning therapeutic effects directly connecting diet and ribosome production are lacking, relationship between these two seems to be plausible.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that beneficial effects mediated by fasting, in particular by CR, do not involve a single gene, a pathway or a unique molecular mechanism. The benefits are due to the negative regulation of nutrient-signaling pathways, including insulin-like growth factor 1 (IGF-1) pathway and its effector extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase (PI3K), which are known to modulate important proliferation pathways (Cangemi et al 2016). Furthermore, it is well known that genomic instability is a distinctive feature of cancer, and CR tumor response seems to play a key role for the maintenance of genomic integrity (Robertson and Mitchell 2013;Duan et al 2017).…”
Section: Molecular Pathways Involved In Dietary Restriction and Cancementioning
confidence: 99%
“…This protein is able to modulate the expression of genes involved in oxidative metabolism, stress resistance, and longevity (Cangemi et al 2016). It has been observed that DR-sensitive cells show a decrease in AKT cytoplasmic levels.…”
Section: Correlations Between Dr and Igf-1 Insulin And Cancermentioning
confidence: 99%
See 1 more Smart Citation